La responsabilidad social y su impacto en la situación financiera y económica de la cooperativa de ahorro y crédito "León XIII" en la ciudad de Trujillo - año 2014 - Quiroz Gálvez, Paola Inés (2016)
This research paper pursues objective: To determine the impact of social responsibility in the financial and economic situation of the credit union Lion XIII in the city of Trujillo- in the year 2014. Whereas social responsibility is one of the main innovations in the achievement of objectives and goals of companies, by the multiple benefits which accrue to all stakeholders. The study was based on theoretical foundations drawn primarily from the literature survey. Research has developed into 7 chapters, which include: Introduction, research design, results, discussion, conclusions, recommendations and References. To achieve this purpose, the descriptive method of applied character was used; Using the methods and techniques of: interview, survey and documentary analysis. Coming to the conclusion that the social responsibility carried out by the cooperative León XIII has a significant and positive impact on the financial and economic situation of the same.